The Correspondence of Charles Darwin - Darwin, Charles 1809-1882 (The Correspondence of Charles Darwin, 2023)
This volume is part of the definitive edition of letters written by and to Charles Darwin, the most celebrated naturalist of the nineteenth century. Notes and appendixes put these fascinating and wide-ranging letters in context, making the letters accessible to both scholars and general readers. Darwin depended on correspondence to collect data from all over the world, and to discuss his emerging ideas with scientific colleagues, many of whom he never met in person. The letters are published chronologically. Darwin died in April 1882, but was active in science almost up until the end, raising new research questions and responding to letters about his last book, on earthworms. The volume also contains a supplement of nearly 400 letters written between 1831 and 1880, many of which have never been published before.